Ventricular pressures in phonating excised larynges - Alipour, Fariborz (Acoustical Society of America, 2012)
Pressure in the laryngeal ventricle was measured with a beveled needle connected to a pressure transducer in excised canine larynges. Air pressures within the ventricle were obtained for different adduction levels of the true vocal folds (TVFs), false vocal folds (FVFs), and subglottal pressures (Ps). Results indicated that the air pressures in the ventricle appear to be strongly related to the motion of the FVFs rather than to the effects of TVF vibration. Both dc and ac pressures depend on FVF adduction, amplitude of motion of the FVFs, and whether the FVFs touch each other during the vibratory cycle. Mean and peak-to-peak pressures in the ventricle were as high as 65% of the mean and peak-to-peak Ps, respectively, when the FVFs vibrated with large amplitude and contact each cycle. If the glottis was not closed, a medial movement of the FVFs appeared to create a positive pressure pulse on the Ps signal due to an increase in the laryngeal flow resistance. The electroglottograph signal showed evidence of tissue contact for both the TVFs and the FVFs. The study suggests that the laryngeal ventricle acts as a relatively independent aero-acoustic chamber that depends primarily upon the motion of the FVFs.